2020
DOI: 10.1101/2020.09.10.291294
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dissociable components of oscillatory activity underly information encoding in human perception

Abstract: Brain decoding can predict visual perception from non-invasive electrophysiological data by combining information across multiple channels. However, decoding methods typically confound together the multi-faceted and distributed neural processes underlying perception, so it is unclear what specific aspects of the neural computations involved in perception are reflected in this type of macroscale data. Using MEG data recorded while participants viewed a large number of naturalistic images, we analytically separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…This is due to the fact that the instantaneous phase information contained within the original EEG signal is discarded during the analytic power envelope computation (see Appendix B for further details). This approximation is employed in recent literature [72][77] to remove instantaneous phase from certain brain oscillations and to study how this phase information contributes to decoding performance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the fact that the instantaneous phase information contained within the original EEG signal is discarded during the analytic power envelope computation (see Appendix B for further details). This approximation is employed in recent literature [72][77] to remove instantaneous phase from certain brain oscillations and to study how this phase information contributes to decoding performance.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, if there is no evidence of temporal generalization, different patterns of activity can be inferred [57]. However, a recent study demonstrated that this interpretation is not always valid, suggesting that this phenomenon can be explained as an artefact of the manner in which the decoding accuracy provided by different components of the signal combine to bring about the overall decoding accuracy [72]. Regardless of the previously selected type of analysis (MVPA or MVCC), the calculation of the temporal generalization matrix can be enabled in the MVPAlab configuration structure as follows:…”
Section: Methodsmentioning
confidence: 99%
“…demonstrated that voltage amplitude and alpha-band power both reliably decoded attention orientation, however alpha-band power was more associated with attention orienting in space while voltage amplitude signaled perceptual processes associated with attention. However, these frequency components must be extracted over a temporal window, thereby resulting in some loss of temporal resolution and increase in the potential dimensionality of the data ( Vidaurre et al, 2020 ).…”
Section: Mvpa Implementationmentioning
confidence: 99%
“…However, these frequency components must be extracted over a temporal window, thereby resulting in some loss of temporal resolution and increase in the potential dimensionality of the data (Vidaurre et al, 2020).…”
Section: Choosing Response Features To Be Used For Classificationmentioning
confidence: 99%